2020
DOI: 10.1177/1012690220943140
|View full text |Cite
|
Sign up to set email alerts
|

The attitudes of collegiate coaches toward gay and lesbian athletes in Taiwan, Hong Kong, and China

Abstract: This study focused on the attitudes of 14 collegiate coaches toward gay and lesbian athletes in Taiwan, Hong Kong, and China and the experience these coaches have had with such athletes. Interview results revealed that different levels of progress in the advocacy for gender equity education and/or sexual minority topics had affected the coaches’ attitudes toward gay and lesbian student athletes. However, with increased contact, the coaches became more inclusive and tolerant toward student athletes with differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…In China, very few LGBTQ athletes have come out publicly. Despite this, recent research has shown that female bisexual student-athletes are better able to explore intimate relationships after prolonged exposure to athletic training and competition (Xiang et al, 2023) and that coaches in China become more accepting and tolerant of student-athletes of different sexual orientations (Tseng and Sum, 2021). These findings suggest that sport can be a more welcoming environment for sexual minorities.…”
Section: Contextualization Of Gendered Sport and Sexuality In Chinamentioning
confidence: 99%
See 1 more Smart Citation
“…In China, very few LGBTQ athletes have come out publicly. Despite this, recent research has shown that female bisexual student-athletes are better able to explore intimate relationships after prolonged exposure to athletic training and competition (Xiang et al, 2023) and that coaches in China become more accepting and tolerant of student-athletes of different sexual orientations (Tseng and Sum, 2021). These findings suggest that sport can be a more welcoming environment for sexual minorities.…”
Section: Contextualization Of Gendered Sport and Sexuality In Chinamentioning
confidence: 99%
“…However, these findings are primarily based on a Western framework of sexual modernity that is "fueled by a powerful rhetoric of identity-based pride and public visibility" (Engebresten, 2015: 91), and may not generalize to non-Western contexts, such as China. Although same-sex relations are still largely taboo in the leading sports organizations and discourse in China (Tseng and Sum, 2021), the growing diversity and multiculturalism of sport in metropolitan cities is fostering the growth of grassroots sports groups for sexual minority individuals. These grassroots sports groups can glimpse the experiences of sexual minority individuals engaged in Chinese sports (sub)culture.…”
Section: Introductionmentioning
confidence: 99%
“…While there has been significant improvement in society's attitudes towards homosexuality, social progress is an uneven social process (Anderson, 2009). Research outside the UK and the US, for example, shows that gay male athletes report homophobic bullying, negative comments, and, consequently, higher rates of dropout compared to straight men (see Baiocco et al 2018;Piedra, Garcia-Perez and Channon 2017;Tseng and Kim-Wai Sum 2020). Both qualitative and quantitative research has also shown that higher levels of prejudice is evident among BME men: Watt and Elliot (2019) show that, in the UK, even though attitudes toward homosexuality in BME communities had changed, they remained less progressive than White communities.…”
Section: The Rise and Fall Of (Sporting) Homophobiamentioning
confidence: 99%
“…Otherwise, Judicial Yuan Interpretation No.748 would automatically become one of the laws based on the current version and recommendation. As a result, on 24 th May 2019, the same-sex marriage law took effect, which allowed same-sex couples to marry in Taiwan (D. T. Chang, 2020;Fell, 2019;Tseng & Sum, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Although the government and the Judicial Yuan offered legal protection for the rights of LGBT individuals and groups in Taiwan, the concepts and behaviours of members of the general public may or may not be influenced by the decisions of the government (D. T. Chang, 2020;Fell, 2019;Tseng & Sum, 2021). In other words, LGBT individuals and groups may continue to experience stress, challenges, and discrimination due to their sexual orientation, regardless of their location and background (Kuan, 2019).…”
Section: Introductionmentioning
confidence: 99%